2020
DOI: 10.3390/pr8070786
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Jatropha curcas L. as Biodiesel Feedstock in Malaysia: A Concise Review

Abstract: Fluctuation in fossil fuel prices and the increasing awareness of environmental degradation have prompted the search for alternatives from renewable energy sources. Biodiesel is the most efficient alternative to fossil fuel substitution because it can be properly modified for current diesel engines. It is a vegetable oil-based fuel with similar properties to petroleum diesel. Generally, biodiesel is a non-toxic, biodegradable, and highly efficient alternative for fossil fuel substitution. In Malaysia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Due to the growing concern toward the competition for food, land, and water resources to produce first-generation bioenergy crops (for example, corn, sugarcane, and soybean), second-generation feedstocks of non-edible oil sources (such as Jatropha, mahua, caster) have gained much attention due to their widespread adaptability, even in adverse climatic and soil conditions of arid and semi-arid regions [2,9]. Further, they have a high oil content between 63.2-66.4%, which is much higher than that of soybean (18.6%), linseed (33.3%), and palm kernel (44.6%) [125]. Studies revealed that approximately 1.5-2.0 million ha of Jatropha have been planted in the last 5-7 years, resulting in around 13 million ha in 2015, and India is a leading country in terms of its cultivation (~73%), followed by Southeast Asia (21%) and Africa (6%) [2].…”
Section: Biodiesel Production Potential Of J Curcasmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the growing concern toward the competition for food, land, and water resources to produce first-generation bioenergy crops (for example, corn, sugarcane, and soybean), second-generation feedstocks of non-edible oil sources (such as Jatropha, mahua, caster) have gained much attention due to their widespread adaptability, even in adverse climatic and soil conditions of arid and semi-arid regions [2,9]. Further, they have a high oil content between 63.2-66.4%, which is much higher than that of soybean (18.6%), linseed (33.3%), and palm kernel (44.6%) [125]. Studies revealed that approximately 1.5-2.0 million ha of Jatropha have been planted in the last 5-7 years, resulting in around 13 million ha in 2015, and India is a leading country in terms of its cultivation (~73%), followed by Southeast Asia (21%) and Africa (6%) [2].…”
Section: Biodiesel Production Potential Of J Curcasmentioning
confidence: 99%
“…The quantities of each fatty acid present in vegetable oils determine the properties of the triglyceride and biodiesel fuel [1,125]. There are three main types of fatty acids present in triglycerides, namely saturated (Cn:0), monounsaturated (Cn:1), and polyunsaturated with two or three bonds (Cn:2,3).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…The corn can be grown and can be harvested in months, and can be planted again, and it is suitable to produce in Malaysia because of warm and rainy season during the year. However, Asian has a competition with the edible oils market, so they explore non-edible seed oil, such as jatropha and pongamia as biodiesel raw oils [19]. But the gestation period of a couple of years are needed before these plants start producing seeds and oil.…”
Section: Introductionmentioning
confidence: 99%
“…The proper way of energy distribution and considering economic and environmental impact may mitigate the drawbacks (Kashem et al, 2018b(Kashem et al, , 2021aTabassum et al, 2016Tabassum et al, , 2018. Moreover, people can use less energy through green buildings (Che Hamzah et al, 2020;Kashem et al, 2021b;. According to researchers, wind energy is still the best way to harness renewable energy.…”
mentioning
confidence: 99%